Resistência de união de cimentos resinosos em superfície de cerâmica de Y-TZP após aplicação de filme vitrocerâmico - Antunes, Débora Pinto [UNESP] (2014)
The bond strength of resin cements Panavia F (P) (Kuraray) and RelyX U200 (R) (3M ESPE) to zirconia using three different surface treatments: 1 - triboquemical silicatization (ST); 2 - glaze (G) 3 - bioactive glass (VBA) was compared. Blocks of Zirkonzahn system were cut producing 90 smaller blocks (5 x 4 x 3 mm). The blocks were polished with water finegrained 1000 and 1200 sandpaper in Politriz and cleaned with 96% isopropyl alcohol for 5 min. The Rocatec Soft was etched with 2.8 bar, in a perpendicular way and a distance of 10 mm for 25 s in a circular motion. The Akyzent Glaze Spray was sprayed by 2s and then sintered in oven Vacumat (Vita) according to manufacturer's recommendations. After application of 1 drop of bioactive glass, the material was dried and sintered at 1200 °C. In all groups was applied silane coupling agent Monobond- S (Ivoclar Vivadent). In groups 3, 4, 5 and 6 the surface was first etched with 5% hydrofluoric acid (HF) and then silanized. The cementing was carried out with a device (Ultradent), producing cured cement cylinders of 2 x 1mm. After 24 h the specimens were aged in thermocycler with 5,000 cycles at a temperature of 5 and 55 ºC and subjected to microshear test on Shear Bond Tester (Bisco). VBA was analyzed by means of DTA, XRD and EDS. Optical profilometry (PO) was performed to obtain roughness. After fracture the samples were analyzed through SEM. It was found that XRD revealed the formation of a glass ceramic film. DTA shows that the temperature of 1200 °C is the most suitable for sintering. DRX showed the formation of a glass ceramic film. According to ANOVA, the interaction effect was significant (p = 0.003 < 0.05). The test for multiple comparison of means, Tukey (5%) showed that the TBS (MPa) for VBA were significantly higher than the other groups (with 26.94 ± 3.50 to P and 28.36 ± 3.32 to R), regardless cement kind used. The lowest result...